2014
DOI: 10.1093/ofid/ofu036
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Viral Hepatitis E Infection in a Tertiary Care Hospital in Mysore, South India

Abstract: Background. In this study, we aimed to explore the clinical and epidemiological profile of all patients with hepatitis E virus (HEV) who were admitted to a tertiary care hospital in Mysore, India and to further assess various factors that influence the prognosis of these patients.Methods. Two hundred ninety patients with HEV infection were included in the study and interviewed. They were subjected to clinical examination and laboratory investigations, including complete hemogram, renal, and liver function test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
6
7
0
Order By: Relevance
“…Our findings are similar to other documented studies [2, 3, 5, 15, 21]. It is well known that the symptoms of HEV infection are more common and apparent in adults, whereas children have asymptomatic infections [3, 22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are similar to other documented studies [2, 3, 5, 15, 21]. It is well known that the symptoms of HEV infection are more common and apparent in adults, whereas children have asymptomatic infections [3, 22].…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study from central India that documents a prevalence of 24.9% of HEV infection in the suspected cases, indicating that HEV is a leading aetiological agent among hepatotropic viruses. Several other studies have also reported similar observations from other parts of India [2, 5]. During the study period of 3 years, samples from villages, towns, and cities of 20 districts were found to be positive, indicating widespread cases of HEV in the region.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…High level of liver enzyme indicates on going hepatocytes injury. Similar findings were also observed in other study in India, where significant relationship between higher level of total and direct bilirubin and mortality rate among HEV infected person was observed (21) . The higher proportion of IUDs and preterm babies observed in present study among HEV-infected women was reported before by others also9.…”
Section: Discussionsupporting
confidence: 90%